The Netherlands : Transforming a Market Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
The striking turnaround in the Netherlands economic performance over the past decade and a half has attracted widespread attention. Emerging from deep recession and high unemployment in the early 1980s, the economy shifted to a pace of growth more rapid than that in neighboring economies, and posted a rise in employment close to that in the United States. However, a number of important problems remain to be tackled to further strengthen economic performance in the Netherlands. The material presented in this paper was originally prepared as background for discussions in the IMF Executive Board and takes account of developments through March 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet